Correction: A pH responsive AIE probe for enzyme assays. Issue 3 (22nd January 2018) - Shi, Leilei; Liu, Yufeng; Wang, Qian; Wang, Tiankuo; Ding, Yubin; Cao, Yi; Li, Zhe; Wei, Hui
Abstract : Correction for 'A pH responsive AIE probe for enzyme assays' by Leilei Shi et al., Analyst, 2018, DOI: 10.1039/c7an01710c.